Transactions of Dr. Vanderkemp in the year 1801 - Vanderkemp, Jan (Adam Matthew Digital, 1892)
Two printed articles followed by ms. minutes and reports, from the records of the Wesleyan Methodist Missionary Society, relating to missionary work in Transvaal and Swaziland, 1891-1892